Assessing the contribution of water and energy efficiency in green buildings to achieve United Nations Sustainable Development Goals in Jordan. (December 2018) - Alawneh, Rami; Mohamed Ghazali, Farid E.; Ali, Hikmat; Asif, Muhammad
Abstract: Water and energy efficiency are given high priority in all green building assessment systems. However, a method to assess and improve their contributions to achieve the United Nations (UN) Sustainable Development Goals (SDGs) has not been developed. This research aims to fill this gap. At the time of this research, most certified green buildings in Jordan were under Leadership in Energy and Environmental Design (LEED) v2.2 new construction. The relationships between the LEED v2.2 "water efficiency" (WE) and "energy and atmosphere" (EA) standards and the UN SDGs were explored using a quantitative descriptive methodology. Structured questionnaire surveys yielded 55 responses from Jordanian building industry experts. Pearson's Chi-square and frequency tests were carried out to examine these relationships. We propose a new Comprehensive Contribution to Development Index (CCDI) to assess the contributions of the implementation of LEED v2.2 WE and EA to achieve the UN SDGs. The results show a positive relationship between LEED v2.2 prerequisites and credits in both WE and EA categories with the UN SDGs 6–9, 12–13, and 15, suggesting that the proposed CCDI is a reliable and robust tool for the evaluation of the contribution of water and energy efficiency in LEED v2.2- certified green buildings to achieving the UN SDGs in Jordan. Highlights: The relationships between the LEED v2.2 WE and UN SDGs 6, 8–9, 12–13, and 15 have been identified. The relationships between the LEED v2.2 EA and UN SDGs 7–9 and 12–13 have been identified. Water and energy efficiency in green buildings contribute to achieving the UN SDGs in Jordan.